Counter-Labelling as a Political Act Towards Sustainability : Ecological Transitions in and Through Finnish Folk Music Education - Lamminmäki, Neea; Sæther, Eva; Treacy, Danielle; Westerlund, Heidi (Springer, 2026)
This chapter critically examines the implications of labelling in music education, emphasising that labels construct music educators’ understanding of the world. Labels can equally maintain hierarchies as they can become instruments for activism and transformative institutional processes, thereby offering the potential for counter-labelling as a means of democratisation. The chapter examines the political use of the label ‘folk music’ in music scholarship and explores professional education in folk music in the Nordic countries, and Näppäri music education in Finland, to illustrate how labelling and counter-labelling processes are political acts within institutionalised music education. The chapter highlights the potential for critical counter-labelling to enhance counter-practices and transformative transitions that challenge music educators’ mental models and hierarchical institutional norms, and thus expands the understanding of music education. It argues that labels used in categorising musical genres, students, and pedagogical approaches are dynamic and inherently political, creating both positive and negative consequences, and advocates for a critical examination of labelling processes to encourage music educators to engage in practices that contribute to sustainable social and cultural change.
Keywords: musiikkikasvatus; kansallinen identiteetti; kansanmusiikki